2011
DOI: 10.1038/leu.2010.302
|View full text |Cite
|
Sign up to set email alerts
|

The isotype of the BCR as a surrogate for the GCB and ABC molecular subtypes in diffuse large B-cell lymphoma

Abstract: Gene expression profiling has identified two major molecular subtypes of diffuse large B-cell lymphoma (DLBCL) that are histologically indistinguishable but differ in cure rates. Here, we investigated whether the isotype of the B-cell receptor (BCR) expressed by the tumoral cells correlated with the molecular subtype and survival. Gene expression analysis clustered the 53 patients included in this study into three subgroups, 17 germinal center B-cell-like (GCB) cases, 26 activated B-celllike (ABC) cases and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
47
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 29 publications
(34 reference statements)
9
47
0
1
Order By: Relevance
“…1C). This finding is consistent with previous work demonstrating that ABC but not GCB DLBCL tumors have genetic lesions that disrupt the switch μ region of the IgH locus that is necessary for Ig class-switch recombination (19,24). Of note, the frequency of IgM BCRs among V H 4-34 + ABC samples was nearly 90%, which was higher than in V H 3-7 + samples (77%) and in all other ABC samples (75%) (Fig.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…1C). This finding is consistent with previous work demonstrating that ABC but not GCB DLBCL tumors have genetic lesions that disrupt the switch μ region of the IgH locus that is necessary for Ig class-switch recombination (19,24). Of note, the frequency of IgM BCRs among V H 4-34 + ABC samples was nearly 90%, which was higher than in V H 3-7 + samples (77%) and in all other ABC samples (75%) (Fig.…”
Section: Resultssupporting
confidence: 81%
“…1A). Previous studies also found an enrichment for V H 4-34 in limited sets of DLBCL (18) or non-GCB DLBCL cases (19,20). Besides V H 4-34, the only IgV H that was more prevalent in ABC DLBCL than in GCB DLBCL and normal B cells was V H 3-7, which was expressed in 7.8% of ABC DLBCL cases (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…Reduction of AICDA transcripts would predict a reduction in somatic hypermutation (SHM). Consistent with this hypothesis, BCRs expressed by primary ABC-DLBCLs often are minimally mutated (37)(38)(39), and transgenic FOXP1-overexpressing mice show GCB cell deficiency (34). Other notable GCB cell identity genes directly repressed after FOXP1 KD include (i) IRF8, which is highly expressed in normal GCB and GCB-DLBCL (40) and negatively regulates PC differentiation (41); (ii) GAB1, an adapter that recruits SH2 domain-containing proteins to the ligated BCR (42); and (iii) LRMP, a lymphoid-restricted membrane protein involved in Ag receptor assembly (43) whose overexpression is a GCB-DLBCL classifier (2,43).…”
Section: Foxp1 Directly Represses Gene Signatures Associated With Gcbmentioning
confidence: 68%
“…The GCB/ABC signature was determined by DASL technology with RNA extracted from fresh frozen material as previously reported. 5,6 By this reproducible and robust method, we observed a concordance rate of 70-95% with immunohistochemistry. 5,6 A direct comparison with microarray-based technology using RNA extracted from formalin-fixed paraffin-embedded tissues is ongoing.…”
mentioning
confidence: 80%
“…9 We have previously shown that VH4-34 + DLBCL frequently expressed IgM, frequently displayed the t(3;14)(q27;q32) translocation, and are typically classified in the ABC subtype. 5,10 This suggests that the increase in the proportion of ABC DLBLC with age may reflect a change in the B-cell population during aging. Another hypothesis relates to the putative pathological specificity of DLBCL occurring in elderly patients.…”
mentioning
confidence: 99%